Exploring the indigenous local governance of Manobo tribes in Mindanao - Felix, Ma. Leny E. (Philippine Journal of Public Administration, 2004)
Assessment of the indigenous system of governance with special attention to the Manobo tribes in Mindanao in response to the call for improvement of the present governance system in both local and national levels of the Philippines is the focus of this article. Manobo or Manuvu tribes has been generally referred to as "river people". They comprise various tribes that are considered lumad found in Mindanao. The Manobo tribes had their own indigenous systems and practices in governance which survived even the coming of the colonizers. The author regards these practices as contributions in the context of leadership, participatory mechanisms, conflict resolution and transparency and accountability. The center of governance was the Datu, the peacemaker, the arbiter, judge and leader. He was chosen based on a defined set of criteria that were strictly followed. The relevance of and adherence to the customary laws of the Manobo despite the absence of a written constitution is at the heart of their unity and evidences of transparency and accountability.